Boosting Productivity of Laser Powder Bed Fusion for AlSi10Mg - Silvio Defanti; Camilla Cappelletti; Andrea Gatto; Emanuele Tognoli; Fabrizio Fabbri (Journal of Manufacturing and Materials Processing, 2022)
The Laser Powder Bed Fusion (L-PBF) process is recognized for high-end industrial applications due to its ability to produce parts with high geometric complexity. If lightweighting is one of the main strengths of L-PBF, a weakness is still the trade-off between high mechanical properties and competitive productivity. This objective can be targeted through a fine tuning of the process parameters within the manufacturing window. The paper pursues the combined optimization of part quality and process productivity for AlSi10Mg by going beyond the commonly used approach based solely on volumetric energy density. The effects of hatch distance and scan speed on the two targets were analyzed in detail. The best results were achieved by the adoption of a high scan speed and a low hatch distance, with notably different outcomes for nearly the same energy density.